Clinical application of Baizhu Houpu Decoction in treatment of chronic kidney disease in the Ji Hai year - YUAN Song-zhu; GAO Xia; SI Ting-lin (Linchuang shenzangbing zazhi)
Chronic kidney disease(CKD) is a slowly-progressing disease of chronic disorders of renal structures and functions arising from various causes(renal injury for more than 3 months),which may affect physiological functions of many systems in the human body.Our supervisor investigated the Qi running features and pathogenesis characteristics of patients with CKD,based on the theory of the doctrine of five evolutive phases and six climatic factors,and applied the six Ji-year recipe Baizhu Houpu Decoction to treatment of CKD patients and achieved good efficacy.The study has provided a new approach and method for treatment of CKD.